Combining several thermal indices to generate a unique heat comfort assessment methodology - Wissam EL Hachem; Joseph Khoury; Ramy Harik (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The proposed methodology hopes to provide a systematic multi-disciplinary approach to assess the thermal environment while minimizing unneeded efforts. Design/methodology/approach: Different factors affect the perception of the human thermal experience: metabolic rate (biology), surrounding temperatures (heat balance and environmental factors) and cognitive treatment (physiology).This paper proposes a combination of different multidisciplinary variables to generate a unique heat comfort assessment methodology. The variables at stake are physiological, biological, and environmental. Our own heat analysis is thoroughly presented and all relevant equations are described. Findings: Most companies are oblivious about potential dangers of heat stress accidents and thus about methods to monitor and prevent them. This methodology enables the company or the concerned individual to conduct a preliminary assessment with minimal wasted resources and time in unnecessary steps whilst providing a guideline for a detailed study with minimal error rates if needed. More so, thermal comfort is an integral part of sound ergonomics practices, which in turn are decisive for the success of any lean six sigma initiative. Research limitations/implications: This methodology requires several full implementations to finalize its design. Originality/value: Most used heat comfort models are inherently uncertain and tiresome to apply.An extensive literature review confirms the need for a uniform assessment methodology that combines the different thermal comfort models such as the Fanger comfort model (PMV, PPD) and WGBT since high error rates coupled with tiresome calculations often hinder the thermal assessment process.
Keywords: 650; heat index; comfort assessment; WBGT; Fanger Comfort Model; globe temperature